The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1080/15693430701742677
|View full text |Cite
|
Sign up to set email alerts
|

Climate change: a ‘glocal’ problem requiring ‘glocal’ action

Abstract: Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(37 citation statements)
references
References 28 publications
1
30
0
3
Order By: Relevance
“…Second, the multi-layered approach would allow considering horizontal and vertical interactions while bridging levels of governance from global to local (Biermann and Pattberg 2012;Gupta et al 2007). The explicit entrenchment of global commitments with national or sub-national priorities and actions would also foster knowledge production and transfer, while easing the identification of new policy options.…”
Section: The Way Forwardmentioning
confidence: 99%
“…Second, the multi-layered approach would allow considering horizontal and vertical interactions while bridging levels of governance from global to local (Biermann and Pattberg 2012;Gupta et al 2007). The explicit entrenchment of global commitments with national or sub-national priorities and actions would also foster knowledge production and transfer, while easing the identification of new policy options.…”
Section: The Way Forwardmentioning
confidence: 99%
“…In practical terms, our results shown that multilevel governance has become the sine qua non condition of urban climate initiatives, as also noted by many studies Alber and Kern, 2008 ;Betsill, and Bulkeley, 2006 ;Gupta et al, 2007 ;Kern, 2010 ;Scanu, 2014 ;Vasi, 2007). In fact, if it is true that cities have powers and competencies, these do not allow cities to address the full range of climate change aspects.…”
mentioning
confidence: 83%
“…Finally, the notion of multilevel climate governance has a normative dimension that frames the battle against climate change as a multidimensional, "glocal" problem, insofar as it requires joint and coordinated efforts from local, regional, national and supranational bodies (Amundsen et al, 2010 ;Corfee-Morlot, et al, 2009 ;Gupta et al, 2007). As Adger and colleagues (2005) remark of adaptation, actions that seem appropriate at a given scale may be inappropriate at another.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Gupta et al [15] suggest that local municipalities are often able to establish more ambitious goals and policies than national governments, which is particularly evident in regards to climate governance. Furthermore, the goals and policies of city-regions related to the bio-economy can be framed through climate governance, which can help to mobilise actors and coordinate diverse interests.…”
Section: The Role Of City-regionsmentioning
confidence: 99%